Kreativnost pri oglaševanju v športu - Vidmar, Boštjan (Šport (Ljubljana), 2021)
Nowadays, we are accompanied by advertisements everywhere, even in sports. In an overcrowded advertising space, it’s hard to make a creative ad. However, it is important that an image or video that we try to attract the attention of potential users achieves as much reach as possible online for as little money as possible. Therefore, we focused on recommendations for the preparation of image and video material for a successful advertisement on digital channels.
Keywords: advertising; content; creativity; kreativnost; oglaševanje; sport; šport; video advertising; video oglasi; vsebina